2009
DOI: 10.1253/circj.cj-08-0945
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Transient Receptor Potential Vanilloid 1 Impaires the Postischemic Recovery of Diabetic Mouse Hearts

Abstract: iabetes mellitus (DM) is one of the most important risk factors of cardiovascular diseases, and numerous patients who are afflicted with diabetes usually suffer the diffused stenosis of coronary arteries, leading to dreadful consequences such as myocardial infarction and cardiomyopathy. Non-invasive evaluation tools such as Doppler echocardiography demonstrate the impairment of cardiac function in diabetic animal models as well as in diabetic patients, 1,2 whereas the mechanism is still not well elucidated.Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
2
28
1
Order By: Relevance
“…In the case of TRPV1, which is mainly expressed at cardiac sensory neurons and activates nociceptors to detect tissue ischemia [39], its expression has been found diminished in diabetes [40]. In this sense, alteration of TRPV1 may impair post-ischemic recovery of diabetic mouse hearts [46]. Finally, very recent data argue in favor of TRPM2 participation in the protection of hearts against I/R injury via reducing ROS generation and increasing ROS scavenging capability in adult cardiomyocytes, by maintaining normal mitochondrial function [43].…”
Section: Ca 2+ Entry/influxmentioning
confidence: 99%
“…In the case of TRPV1, which is mainly expressed at cardiac sensory neurons and activates nociceptors to detect tissue ischemia [39], its expression has been found diminished in diabetes [40]. In this sense, alteration of TRPV1 may impair post-ischemic recovery of diabetic mouse hearts [46]. Finally, very recent data argue in favor of TRPM2 participation in the protection of hearts against I/R injury via reducing ROS generation and increasing ROS scavenging capability in adult cardiomyocytes, by maintaining normal mitochondrial function [43].…”
Section: Ca 2+ Entry/influxmentioning
confidence: 99%
“…45 Studies on glucose effects on neuropeptides are limited thus far, but there are indications that either dextrose elevations or a related reduction in insulin levels downregulate the activity of the transient receptor potential vanilloid type 1 (TRPV1) receptor which reduces production of pain producing (substance P) and degenerative (calcitonin gene-related peptide [CGRP]) neuropeptides. [46][47][48] …”
Section: Consideration Of Possible Mechanisms and Explanationsmentioning
confidence: 99%
“…7 The other candidate might be TRPV1, which plays a role in neurosensory mechanotransduction involved in cardiovascular homeostasis. 2,28, 29 Although our data support a role for ASIC3 in blood volume control, obtaining direct evidence of the involvement of ASIC3 in sensing the volume receptor stretch is still a challenge. Previous studies have demonstrated that loss of Asic3 in mice alters mechanotransduction in the gastrointestinal tract, skin, and auditory system.…”
Section: Discussionmentioning
confidence: 74%